(3JPcQI GdcMGdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s
(3ChdgG (B:s
(3DCi UGMHgG GdTF CcHQ eeG gh GdYdGL (B: (3jLH ChdG Cf JSCd Yf GdJOHjQ GdeJbOe hjchf GdYdGL HMSHg s
(3BNQgG (B:s
(3GSJYed GdeGA GdYPH GdaGJQ Ydi GdhLg hGdQCS hCeG GdMGOK Yf hQe aYGdLg HGdQjGVI hPdc GdQCS hGdhLg hGdYjf GSJYed JeGe GdYdGLGdeVjb GdPj jMOK Yf s
(3HBNQgG bQGAI Ydi CHj efUhQ GdeHGQc Hf GdUHGZ GdWHjHs
(3SfI (B676(3g`s
(3hHYV ChQGb GdfSNI eced HNW MOjKs
(3fSNI SGOSI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B50 s
Keywords: (3GdWHs